Effect of Water Stress on Cortical Cell Division Rates within the Apical Meristem of Primary Roots of Maize. - Sacks, M. M. (1997)
We characterized the effect of water stress on cell division rates within the meristem of the primary root of maize (Zea mays L.) seedlings. As usual in growth kinematics, cell number density is found by counting the number of cells per small unit length of the root; growth velocity is the rate of displacement of a cellular particle found at a given distance from the apex; and the cell flux, representing the rate at which cells are moving past a spatial point, is defined as the product of velocity and cell number density. The local cell division rate is estimated by summing the derivative of cell density with respect to time, and the derivative of the cell flux with respect to distance. Relatively long (2-h) intervals were required for time-lapse photography to resolve growth velocity within the meristem. Water stress caused meristematic cells to be longer and reduced the rates of cell division, per unit length of tissue and per cell, throughout most of the meristem. Peak cell division rate was 8.2 cells mm-1 h-1 (0.10 cells cell-1 h-1) at 0.8 mm from the apex for cells under water stress, compared with 13 cells mm-1 h-1 (0.14 cells cell-1 h-1) at 1.0 mm for controls.